Moving forward an Inclusive Education: Approaches and Opportunities for Learners with Disabilities - Houda Boumediene; Fatiha Kaid Berrahal (The Journal of Studies in Language, Culture and Society, 2019)
The current research paper examines approaches and opportunities for learners with specific educational demands in an effective inclusive education. It differentiates inclusive education from special education and segregation and goes deeply to provide a comprehensive meaning to the term inclusion. This conceptual research aims to describe and clarify Inclusive education as a concept, which necessitates different approaches to be realized. Inclusion supports the right that every child is valued equally and deserves the same opportunities and experiences to education. Some of the benefits of this inclusive education for both children and families include multicultural learning environment in which learners with disabilities develop a positive understanding of themselves and others, socialization and learning by being together, and also the development of the child’s academic skills. Approaches identified for suitable inclusive education are placing the child in an appropriate place, practicing cooperative learning with no special classes or separate schools. Obstacles can be overcome by breeding awareness on what inclusion is and making inclusion a reality’ s benefits should be supported by the society, schools and families. This paper suggests that inclusive education keeping deserves to be taken into consideration in re-structuring the curriculum to meet varying needs within the classroom.